KONTROL BISING AKTIF MEDAN SUARA BEBAS MENGGUNAKAN SUMBER SEKUNDER MULTIPOL - Kusni, Muhammad
The commercial feasibility of active noise reduction is very promising because it can be functionally a complement of passive noise reduction. For several cases, active noise control is more economical and more effective in reducing noise than passive noise control. The active noise reduction can also selectively reduce noise. Of course, the features mentioned above are not without problem. The active noise reduction using a conventional secondary source can become very complicated when significant noise level reduction is required, because it requires a large number of secondary sources. The active noise reduction becomes less effective for the reduction of highfrequency noise. A multipole secondary source method has been proposed in this research to overcome the problems mentioned above. The method is based on the Taylor series expansion to determine higher order secondary sources used in the cancellation, such as dipole, quadrupole, octopole, and so on. By using higher order secondary sources much more significant noise reduction can be obtain. A numerical simulation of noise reduction in a free field was conducted using the method. Test cases are shown using dipole and other combination as secondary sources. The result shows that a noise reduction may be obtained up to 50 dB at 200 Hz.